Mycosis fungoides: a rare case report - Panmei, Ruby; Devi, Angom Ronibala; Babu B., Mohan; Devi, Yumkhaibam Sobita (International Journal of Research in Medical Sciences, 2024)
Lymphoproliferative disease has many sub-types but the most-commonest subtype of cutaneous T-cell lymphoma is mycosis fungoides (MF). When it presents as solitary or oligo-lesional lesion, radiation therapy is considered potentially curative. This paper presents a case of 17-year-old female who developed two skin lesions in her left knee. She was diagnosed as a case of MF in patch stage. Localised radiation therapy was given to the lesion. MF prognosis depends overall on its stage and is usually better in the early stages. MF is rare and often requires a clinical-pathological correlation for its diagnosis, which is often delayed, especially in the early forms.